HYGIENIC RECOMMENDATIONS FOR PREVENTING RISK FACTORS IN THE DAILY ROUTINE OF PRESCHOOL-AGE CHILDREN - Nizom Jumakulovich Ermatov; Berdiev Olim Dovronovich (The latest pedagogical and psychological innovations in education, 2026)
The organism of preschool-age children is in a phase of active growth and development. Disruptions in daily routine and healthy nutrition, decreased immunity, and susceptibility to infectious diseases are observed during this period 1,2,41,2,4.